Adaptation of Activity Theory Framework for Effective Online Learning Experiences: Bringing Cognitive Presence with Teaching and Social Presences in Online Courses - AYTAC GOGUS (Online Learning, 2023)
The study logic is constructed on offering online courses can be seen a new way of enhancing a cognitive presence besides teaching and social presences of the Community of Inquiry (CoI) model. Creating and enhancing cognitive, teaching, and social presences require an innovation for teachers during planning, implementing, and evaluating their online courses. As teachers develop their own expertise in teaching online, so hopefully they contribute to enhance cognitive, teaching, and social presences for effective online learning. This study reviews models for online learning experiences and propose a new model by adapting activity theory in the online learning management context. This study presents a framework aims to adapt activity theory to present how to design, develop, implement, and evaluate online courses that enhance a cognitive presence besides teaching and social presences. This study suggest to consider objects as online learning experiences with cognitive presence, teaching presence, social presence since enhancing cognitive presence, teaching presence and social presence means to reach learning outcomes of the course besides matching the required qualifications of higher education.